Evaluación del potencial de biomasa residual del ganado vacuno para el aprovechamiento energético en la hacienda Galpón del cantón Salcedo provincia de Cotopaxi año 2013. Diseño de un biodigestor alternativo para este propósito. - Santos Benavides, Williams Roberto (2015)
At present investigation was carried out a theoretical and experimental study of the energy potential of residual biomass of cattle on the Galpón farm, in order to take advantage of biological waste in a bio-digester to obtain a renewable energy, which helps to reduce the greenhouse gases, like CH4 issued into the atmosphere by the aerobic decomposition of animal excrement. The literature reviewed was highlights the objectives achieved in different works in terms of the methodology used to characterize residual biomass of cattle and energy analysis, refers, reflecting technical-economics and environmental data useful for the proposal of a fixed dome bio-digester. Part of the experimental study of the anaerobic process of organic matter (manure), where the characterization of the: level of pH, is temperature of biodegradation, hydraulic retention time (THR), amount of particles of methane in the biogas and the bio-fertilizer nutrient; there procedures were carried out for evaluation and residual biomass of the cattle on the Galpón farm, with the purpose of obtaining two primary benefits: reducing the direct emanation of gas methane into the atmosphere and introduce a new type of renewable energy. The bio-conversion process was implemented in two biodigester type "Batch" with and without thermal insulation, where is interfered with the technology of the monitoring and data acquisition in real time, allowing getting the actual data of the anaerobic process, basic parameters to determine the quality of production of biogas and bio-fertilizer to be used by the Galpón farm; and, through the experimental calorimetric method determined the calorific power of the biogas produced by the prototypes of bio-digesters type "Batch", applying a thermodynamic property. Finally, the financial evaluation confirmed the feasibility of implementing a fixed dome bio-digester, where is obtained a net present value (NPV) positive, for an internal rate of return (IRR) exceeding the reference rate imposed by the Central Bank of Ecuador (BCE), which will produce economic profits to finance medium and long term.